HUBUNGAN KARAKTERISTIK DEMOGRAFI DENGAN TINGKAT KECEMASAN PADA PASIEN POST COVID-19 - Lusi Nurhayati; Friska Sinaga; Lidwina Triastuti Listianingsih; Elizabeth Ari Setyarini; Florentina Dian Maharina (Jurnal Kesehatan, 2023)
Covid-19 is a new case, namely an infectious disease caused by (SARSCov-2). The impact is felt physically and psychologically, such as anxiety. The purpose of this study was to determine the relationship between demographic characteristics and anxiety levels. This research was conducted quantitatively with a descriptive and cross sectional design. An online survey with an accidental sampling technique was carried out via WhatsApp on post-Covid-19 patients for 1 month. The sample collected amounted to 319 respondents. The data collected were analyzed using chi square and spearman rank tests. The results: 84% of respondents were not anxious, 16% of respondents experienced anxiety. The results of the analysis stated that there was a relationship between sources of information (p value = 0.016), comorbid status (p value = 0.000) and vaccine status (p value = 0.000) and there was no relationship between age (p value = 0.270), gender (p value = 0.000) = 0.600), education level (p value = 0.904), frequency of exposure to Covid-19 (p value = 0.433) and post-Covid-19 symptoms (p value = 0.705) with anxiety..